RELASI NEGARA DAN AGAMA - Hufron (Faculty of Law, University of Dr. Soetomo, 2017)
Basically the normative judical of the State Administration System of the Republic of Indonesia after the amandement of the 1945 Constitution relating to the regulation of the relationship between the State and Religion is sufficient and meaningful, beginning in the Preamble to the 1945 Constitution, and the articles in the body, starting Article 9, Article 22 D, Article 24 Paragraph (2), Article 28E Paragraph (1), Article 28J Paragraph (2), Article 31 Paragraph (3) and (5) of the 1945 Constitution. At the practical level, the dynamics of State and Religious Relation Post-Change of 1945 Constitution shows a more dynamic relationship and harmonious existence of symbiotic-mutualism between the role of the Government of Indonesia and Religion in realizing the goals of the state government as stated in the Preamble of the 1945 Constitution. This is proven factually in the Indonesian constitutional practice, various laws and regulations based on or adopting the values of the substance of Islam. Such as Marriage Law, Zakat Law, Religious Judicature Law, Wakaf Law, Hajj Administration Law, Sharia Banking Law, State Sharia Securities Law, and the birth of various Regional Regulations (Perda) based on Shariah (qonun) in the current era of regional autonomy.